Application of the Canon 320 Row Variable Helical Pitch CTA System Combined with Iterative Reconstruction Technology for Lower Limb Vascular Imaging - Wenchao JI; Weili TIAN; Wenya LIU; Lianghao HE; Jian YANG (CT Lilun yu yingyong yanjiu)
Objectives: To investigate the image quality obtained using the Canon 320 row variable helical pitch (vHP) computed tomography (CT) system combined with iterative reconstruction technology for lower limb angiography and the radiation exposure to patients. Methods: From March 2023 to June 2023, we enrolled 40 patients who were treated at our hospital for suspected arterial vascular disease of the lower limbs. The patients, who all underwent CT angiography of the lower limb arteries, were divided into two groups (A and B; 20 patients/group) through double-blind random grouping. Both groups were treated with 370 mg/mL of the contrast agent iodoparol at a tube voltage of 120 kV. A dual-cylinder high-pressure syringe was used to inject 90 mL of the contrast agent into the median elbow vein at a flow rate of 5 mL/s. The scanning range extended from the level of the abdominal aorta to the toe. For Group A, the Canon 320 row vHP system was used, with a large pitch from the abdominal aorta to the popliteal fossa and a small pitch from the popliteal fossa to the tip of the heel. The images were reconstructed using iterative reconstruction technology. For Group B, conventional pitch technology was used for full scanning and the Filtered BackProjection method for image reconstruction. The subjective image quality, signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), CT value, effective radiation exposure, and contrast medium iodine intake at four measuring points of the abdominal aorta and common iliac, upper femoral, and popliteal arteries were compared between the two groups. The t-test was used to compare the objective evaluation index, effective radiation exposure, and contrast agent iodine intake values between the two groups, whereas the Mann-Whitney U test was used to compare the subjective scores. Results: There were no significant differences between the two groups in terms of objectively evaluated image quality, SNR, and CNR of the abdominal aorta and common iliac, upper femoral, and popliteal arteries. Group A had significantly higher vascular CT values than Group B. Moreover, the patients in Group A were significantly less exposed to radiation (9.18±0.36) mGy than those in Group B were (18.1±0.00) mGy. Conclusion: The Canon 320 row vHP system combined with iterative reconstruction technology ensured good image quality and significantly reduced patient exposure to radiation, thereby improving the safety of CTA, and can be widely used in clinical practice.